What “Persuades” God to Respond to the Psalmist’s Cry? Use of Rhetorical Devices Related to “Vows of Future Praise” in Some Psalms of Lament - Dickie, June F. (Old Testament Essays, 2021)
Psalms of lament characteristically include affirmations of trust and sometimes a vow to praise God in the future. This article questions the motivation behind such vows by looking carefully at whether future praise is conditional on God’s positive response and what other rhetorical devices are linked to the promise God makes. Attention is given to the nature of praise and lament psalms (considering the power dynamic) and foundational principles of Persuasion Theory. Five biblical psalms of lament are considered, with particular attention to their use of a vow and other persuasive tactics to encourage God to intervene. Although a vow of future praise (and other persuasive tactics) may be used, the psalmist’s most critical means of persuasion (as apparent in Ps 88) is the character of the psalmist’s covenant-partner.
free
Keywords: Persuasion; Psalms of lament; Rhetorical devices; Vows